Fascin and esophageal squamous cell carcinoma. Issue Volume 1:Issues 3(2017) (25th September 2017) - Cheng, Yinwei; Xie, Jianjun; Zeng, Famin; Nie, Pingjuan; Wu, Bingli; Du, Zepeng; Pan, Feng; Wu, Jianyi; Xie, Lei; Zhang, Pixian; Xu, Xiu‐e; Liao, Liandi; et al.
Abstract: In a cancer prevalence survey, China was recognized to have a high incidence of esophageal cancer. Esophageal squamous cell carcinoma (ESCC) is the predominant subtype of esophageal cancer and accounts for the vast majority of cases every year. ESCC cases in China contribute toward nearly half of all new global cases each year. As one of the higher ESCC prevalence regions in China, the Chaoshan District of Guangdong Province is the only area on the Chinese coastline with such a distinguished profile. Our laboratory, which is located in the Chaoshan District, studies the biological function, molecular basis, regulation mechanisms, and clinical significance of abnormally expressed cellular cytoskeleton binding proteins in ESCC, such as ezrin, fascin, LCN2, LOXL2, and DSC2. In the present review, we summarized studies on fascin in ESCC reported by our laboratory and other laboratories around the world. In ESCC, fascin expression is highly upregulated at the mRNA and protein levels, and can serve as an early biomarker for tumor invasion and metastasis. Furthermore, fascin transcription is directly activated through Sp1 binding to its promoter; this process is enhanced through the phosphorylation of Sp1 by the epidermal grown factor‐activated Mitogen‐activated protein kinase (MAPK)/Extracellular signal‐regulated kinase (ERK) (MEK)‐ERK1/2 signaling pathway. Furthermore, the function of fascin is also regulated by post‐translational modifications. For instance, the phosphorylation of several amino acid residues of fascin inhibits ESCC cell behavior and filopodia formation. However, whether other types of fascin modifications exist remains unknown and requires further study.